Exercise prehabilitation in lung cancer: Getting stronger to recover faster. Issue 8 (August 2021) - Avancini, Alice; Cavallo, Alessandro; Trestini, Ilaria; Tregnago, Daniela; Belluomini, Lorenzo; Crisafulli, Ernesto; Micheletto, Claudio; Milella, Michele; Pilotto, Sara; Lanza, Massimo; Infante, Maurizio Valentino
Abstract: Despite several recent advances, lung cancer surgery is still associated with potentially severe postoperative complications. It has been suggested that preoperative exercise training could render patients with borderline functional parameters eligible for surgery, improve perioperative outcomes and that these benefits might reduce healthcare costs. Nevertheless, given the substantial heterogeneity of the available studies, no specific guidelines for preoperative exercise training have been released so far. This narrative review aims to provide an overview of the potential benefits of exercise training in the preoperative period as a central intervention for lung cancer patients. In detail, the effects of exercise (with different regimens) were evaluated in terms of physical functions, patients' eligibility for curative surgery, postoperative complications and length of stay, with an exploratory focus on healthcare costs and long-term outcomes. Furthermore, a feasible approach for every-day clinical practice is proposed in order to increase the expected benefit deriving from a more extensive and methodical application of prehabilitation exercise, ideally in the context of a comprehensive approach to lung cancer patients, including nutritional and psychological support. Highlights: Exercise prehabilitation enhances the functional capacity of lung cancer patients; Exercise prehabilitation may decrease postoperative complications and length of hospital stay; Exercise prehabilitation can make eligible for surgery functionally inoperable patients; High-intensity interval training may maximize results quickly and without delaying surgery.